Rectal foreign body: A successful removal at the bedside and detailing of a stepwise management - Eng, David Yeow Gan; Kheng, Hooi Chan; Pramanantha Veerappan; Kian, Joo Sun; Mohd Firdaus Mohd Hayati (International Scientific Literature, Inc, 2021)
BACKGROUND: A rectal foreign body (RFB) can be stigmatizing for patients and present a dilemma for the treating physician. Removal can be challenging owing to the variety of objects introduced. The goals of therapy are to safely remove the RFB and to minimize injury to the bowel. CASE REPORT: A 22-year-old man was referred from a district hospital to our institution after being unable to remove a self-inflicted RFB after sexual gratification. He was hemodynamically stable with a soft and nontender abdomen. A mass was felt in the suprapubic region. Abdominal radiography revealed a well-defined radiolucent object in the pelvic region, which was consistent with a lubricant bottle. No sign of bowel obstruction or perforation was observed. The RFB was successfully retrieved by a combination of transrectal digital manipulation and directed gentle abdominal pressure, allowing for descent of the RFB and transanal traction at the bedside. Various approaches have been described for removal of a RFB, from simple bedside strategies to open surgery for complicated cases. Endoscopy and minimally invasive techniques have also demonstrated a role in formulating a tailored approach. CONCLUSIONS: We describe a successful retrieval of an RFB at the bedside, avoiding unnecessary open surgery.